2019
DOI: 10.1016/j.aquaculture.2019.734419
|View full text |Cite
|
Sign up to set email alerts
|

Production potential of greater duckweed Spirodela polyrhiza (L. Schleiden) and its biochemical composition evaluation

Abstract: The culture technique of greater duckweed Spirodela polyrhiza (L. Schleiden) was standardized in outdoor tanks using three different manures: manure 1-cattle manure, poultry droppings and mustard oil cake, manure 2-urea, potash and triple superphosphate and manure 3-cattle manure, urea, potash and triple superphosphate. Significantly (p<0.05) higher production was recorded in manure 1 compared to others. Manure 1 was subsequently selected for pond culture. In ponds, the production of duckweed was 2020±150 kg h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
3
24
0
1
Order By: Relevance
“…Duckweeds are considered as novel ingredients to replace soybeans, thus reducing the burden of greenhouse gas emissions and alleviating the negative aspects of feed production [ 51 ]. The protein content of duckweeds grown in organic manure is very high, and utilization of duckweed as feed has been suggested as a solution to environmental issues related to manure purification and feed production [ 54 ]. Duckweeds are protein sources that could replace soybean meal and are expected to be used as substitutes to reduce environmental pollution created by expanding soybean cultivation.…”
Section: Duckweeds and Their Utilizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Duckweeds are considered as novel ingredients to replace soybeans, thus reducing the burden of greenhouse gas emissions and alleviating the negative aspects of feed production [ 51 ]. The protein content of duckweeds grown in organic manure is very high, and utilization of duckweed as feed has been suggested as a solution to environmental issues related to manure purification and feed production [ 54 ]. Duckweeds are protein sources that could replace soybean meal and are expected to be used as substitutes to reduce environmental pollution created by expanding soybean cultivation.…”
Section: Duckweeds and Their Utilizationmentioning
confidence: 99%
“…The nine essential amino acids found in the duckweed species are histidine, isoleucine, leucine, lysine, methionine, phenylalanine, threonine, tryptophan, and valine and eleven non-essential amino acids, namely alanine, arginine, asparagine, aspartate, cysteine, glutamate, glutamine, glycine, proline, serine, and tyrosine, were also found in duckweeds (Table 6 ) [ 9 , 15 , 54 , 116 , 122 ]. Amino acid derivatives, such as citrulline, cystathionine, hydroxyproline, γ-aminobutyric acid (GABA), and taurine, were also found (Table 6 ) [ 54 , 122 ].…”
Section: Useful Metabolites In Duckweedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the quantity of protein producible by duckweed is well documented, less work has been done on the quality of duckweed protein (DWP). Several studies have examined the amino acid composition of various duckweeds and concluded that based on its amino acid profile, the quality of DWP is suitable for consumption by fish, poultry, cattle, and humans (Appenroth et al., 2018; Hanczakowski et al., 1995; Sharma et al., 2019). Duckweed can also accumulate trace minerals (K, Ca, Mg, Na, Fe) which are often deficient in the feed available to small livestock farmers (Leng, 1999), as well as micronutrients (iodine and vitamin A) which are commonly deficient in the diets of malnourished people (Valdimirova & Georgiyants, 2014).…”
Section: Introductionmentioning
confidence: 99%